Polygenic risk score of non‐melanoma skin cancer predicts post‐transplant skin cancer across multiple organ types. Issue 8 (31st May 2020) - Stapleton, Caragh P.; Chang, Bao‐Li; Keating, Brendan J.; Conlon, Peter J.; Cavalleri, Gianpiero L.
Abstract: Polygenic risk scores (PRSs) calculated from genome‐wide association studies (GWASs) of non‐melanoma skin cancer (NMSC) in a general, non‐transplant setting have recently been shown to predict risk of and time to post‐renal transplant skin cancer. In this study, we set out to test these findings in a cohort of heart, lung, and liver transplant patients to see whether these scores could be applied across different organ transplant types. Using the PRS from Stapleton et al (2018), PRS was calculated for each sample across a European ancestry heart, lung, and liver transplant cohorts (n = 523) and tested as predictor of time to NMSC post‐transplant. The top PRS, squamous cell carcinoma (SCC) pT1 x 10 −5, (n SNPs = 1953), SCC pT1 x 10 −6, and SCC pT1 x 10 −6 (n SNPs = 1061) were significantly predictive in the time to NMSC, SCC, and basal cell carcinoma (BCC) analysis across organ ( P  = .006, .02, and .02, respectively). We observed here a similar direction of effect and effect size [NMSC HR = 1.31(1.08‐1.59)] to that in the original discovery study with increased polygenic burden leading to a faster time to developing NMSC. In summary, we found that PRS of NMSC calculated from GWAS of NMSC in non‐transplant populations independently replicated in this cohort of heart, lung, and liver transplant.